HEAVY METALS IN CERTAIN COMMERCIALLY IMPORTANT FINFISH OFF MAHIM IN MUMBAI COASTAL WATERS - Agrahari, Raj Kumar; Varshney, P. K.; Purushothaman, C. S.; Padmanabhan, A. K. (Journal of Indian Fisheries Association, 2006)
The coastal water of the metropolitan city of Mumbai has deteriorateddue to the indiscriminate discharge of untreated sewage and industrial waste in huge quantities. Mahim creek is one such locality surrounded by a large number of industrial units discharging heavy metals. The accumulation of the heavy metals Cu, Cd, Zn and Pb in finfishes (Co ilia dussumeri, Lepturacanthus savala, Harpodon nehereus and Johnieops elongate::,) from this locality along with that in the sediment was studied. The rate of accumulation of Cu was high compared to Cd, Zn and Pb. A gradual increase in the bioaccumulation of heavy metals was noticed in fishes with increase in average body weight and length, perhaps due to biomagnification. A declining trend in concentration of heavy metals horizontally from inshore to offshore was observed in these fishes.Keywords : Mahim creek, sewage, Cd, Zn, Pb, Cu